Calcareous nannobiostratigraphy of the Hartha Formation, East Baghdad well No.6, Central Iraq (Sulaimani Journal for Pure and Applied Sciences, 2021)
Fifteen samples of Limestone from the Hartha Formation were obtained from East Baghdad well No.6, Central Iraq, from the depth (2247-2261 meter) about 14 meters thickness. Detail investigation was carried out, from which fifteen species of calcareous nannofossils identified; eleven were descried from other regions and four were left under an open name because of lack of material or rare of samples. The recorded calcareous nannofossil assemblages recognized two biozones these from the lower to the upper part of the section : 1 - Eiffellithus eximius Interval Zone (CC19) part 2- Ceratolithoides aculeus Interval Zone (CC20) part These biozones are correlated with other calcareous nannofossils biozones from both local and regional sections that lead to conclude the age of the Middle Campanian.
Keywords: Calcareous nannofossils; Nannobiostratigraphy; Hartha Formation; Cretaceous; Iraq